2001
DOI: 10.1071/wf01021
|View full text |Cite
|
Sign up to set email alerts
|

Surface burning in a mature stand of Pinus resinosa and Pinus strobus in Michigan: effects on understory vegetation

Abstract: Beginning in 1991, periodic surface fires (frontal fire intensities <200 kW m–1) were introduced into a mixed red pine (Pinus resinosa Ait.) and white pine (P. strobus L.) plantation (dbh 16–60 cm). Replicated plots of 0.4–0.5 ha were either burned three times at biennial intervals (early May of 1991, 1993, and 1995), burned once (early May 1991), or not burned. Measurements were conducted during the 1994 and 1995 growing seasons. The pine overstory was largely unaffected by the fires. The understory on unb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although fire may kill the fronds of D. carthusiana and D. expansa , rhizomes of both species are able to survive single fire events (Ahlgren 1960; Neumann & Dickmann 2001). Investigation of the long‐term effects of fire on the boreal forest understory (Québec, Canada) has shown that D. carthusiana was generally more abundant in the earlier stages of post‐fire succession (De Grandpré, Gagnon & Bergeron 1993).…”
Section: Response To Environmentmentioning
confidence: 99%
“…Although fire may kill the fronds of D. carthusiana and D. expansa , rhizomes of both species are able to survive single fire events (Ahlgren 1960; Neumann & Dickmann 2001). Investigation of the long‐term effects of fire on the boreal forest understory (Québec, Canada) has shown that D. carthusiana was generally more abundant in the earlier stages of post‐fire succession (De Grandpré, Gagnon & Bergeron 1993).…”
Section: Response To Environmentmentioning
confidence: 99%
“…The extent of this species was reduced by logging and fires fed by logging slash, eliminating seed sources and promoting early successional species (Weyenberg et al 2004). Further reductions have been linked to subsequent fire suppression policies, which precluded the frequent periodic ground fires (Neumann and Dickmann 2001) to which the species is well adapted by thick-bark (Van Wagner 1963, Frissell 1973, Johnson 1991, Beverly and Martell 2003 and tolerance of crown scorch (Methven 1971). Over the past 150 years, recruitment into the sapling layer has been poor for P. strobus (Carleton et al 1996).…”
mentioning
confidence: 99%
“…Chemical treatments and livestock grazing have been used as well, but are not as common across agencies. Incorporating fire into forest management can be a practical method since fire was formerly a naturally occurring process that helped maintain open forest conditions and lower loads of hazardous forest fuels (Drobyshev et al 2008b, Neumann andDickmann 2001). Although naturally ignited wildfires and prescribed fires are generally recognized as useful tools, they often have a high risk associated with their implementation (Yoder 2008).…”
Section: Fuels Treatmentsmentioning
confidence: 99%